Effect of Environmental Accounting on Financial Performance and Firm Value of Listed Mining and Oil Companies in the Philippines - Carandang, Jamil C. (Animo Repository, 2020)
Environmental accounting is an emerging topic of research around the globe, but little is known of its practice and importance in the Philippines. This paper aims to determine the effect of environmental accounting on firm profitability and firm value of 24 publicly-listed mining and oil companies in the Philippines from 2012-2016. Panel regression was utilized with cross-sectional and time-series data. Environmental accounting was measured as environmental accounting disclosures and environmental costs reporting. Profitability was measured as net profit margin and return on equity, whereas firm value was measured as Tobin’s Q. Moderating variables used were auditor-firm type, firm size, board size, number of years listed Philippine Stock Exchange (PSE), and location. The major business implication concluded was that environmental accounting disclosure has no significant effect on either profitability or firm value, but when moderated by location, it has a significant effect on return on equity. Environmental costs reporting, on the other hand, has a significant effect on return on equity, but when moderated by firm size, board size, number of years listed in the PSE, and location has a significant effect net profit margin, return on equity, and Tobin’s Q.